Youth Temperament Moderates Associations Between Parental Involvement and Pediatric Type 1 Diabetes Treatment Outcome. (12th March 2022) - Yeo, Anna J; Halpern, Leslie F; Lin, Betty; Riddick, Linda; Sima, Daniela; Wohlfahrt, Kristine M; Jones, Nancy
Abstract: Objective: Both youth self-regulation and quality of parental involvement have been associated with blood glucose levels (HbA1c) of youth with type 1 diabetes mellitus (T1DM). However, it is unclear whether and how youth and parental factors interact in their relation to youth HbA1c. The differential susceptibility hypothesis proposes that youth with high negative affectivity (NA) and low effortful control (EC) may be more susceptible to the deleterious impact of lower quality parenting behaviors but also reap greater benefit from higher quality parenting behaviors. This study investigated whether youth temperament would moderate the link between diabetes-specific parental assistance (e.g., checking blood sugar) or support (e.g., encouraging, praising) and HbA1c among youth with T1DM. Methods: Primary caregivers of youth with T1DM ( N  =   101; M age = 12.02, SD   =   2.43) completed surveys on diabetes-specific parental involvement and youth temperament. Medical information (i.e., HbA1c) was obtained from chart review. Results: Multiple regression analyses indicated that youth NA and EC significantly interacted with parental assistance, but not support. Specifically, higher parental assistance was associated with higher HbA1c among youth with high NA or high EC. High assistance was only linked to lower HbA1c for youth with low NA. Conclusions: Results suggest that optimal levels of parental involvement related to better T1DM outcomes depend on youth's NA or EC. Consistent with the goodness-of-fit framework, when parenting approaches match youth's temperament, youth with T1DM may be better able to maintain lower HbA1c. Family interventions for pediatric T1DM management may take into consideration youth temperament.